Strategic planning for information technology in academic libraries (2005)
As the mission of most libraries' in the electronic age is "accessibility" based library administrators have had to deploy technology as an end. Many academic libraries in Nigeria and across the world have had to invest in technology without planning for it. The rate of obsolencence of technologies, the costs of replacement and updating of the technologies, and the call for accountability by stakeholders are reasons for libraries to creatively plan and implement information technology plans in the context of the institutional goals and mission. It is recommended that appropraite technologies be applied as a means thereby enabling academic libraries to articulate a vision, publicly state a direction, and stay the course despite the numberous distractions faced by library management on daily basis. It is advised that developing an information technology plan is a "manageable" effort.